Ages and Stages Questionnaire: Social–Emotional as a Teacher-Report Measure. (March 2019) - Pooch, Abigail; Natale, Ruby; Hidalgo, Tatiana
Universal screening of social–emotional deficits in preschool children is a promising avenue for detecting children in need of early intervention. Due to the enormity of this task, it is vital that the instruments used in universal screening be brief, inexpensive, and capable of accurately measuring social–emotional development. The Ages and Stages Questionnaire: Social–Emotional (ASQ:SE) fulfills these requirements, but has been established only as a parent-report instrument, which makes it difficult to assess preschool-based child behavior and reporter bias. The current study examined the reliability and validity of the ASQ:SE in a sample of 443 preschool children and their teachers. Overall, the teacher-report ASQ:SE produced promising findings, including adequate internal consistency reliability (α = .73-.74) and strong concurrent validity. Further studies should include discriminant validity analyses, and more representative samples to allow for generalization of results.